Climate and ground temperature relations at sites across the continuous and discontinuous permafrost zones, northern Canada 1 This article is one of a series of papers published in this CJES Special Issue on the theme of Fundamental and applied research on permafrost in Canada. 2 Earth Science Sector (ESS) Contribution 20110128. - Throop, Jennifer; Lewkowicz, Antoni G.; Smith, Sharon L. (Canadian Journal of Earth Sciences, 2012)
Climate – ground temperature relations are examined under a range of conditions for 10 sites across northern Canada. The sites are located between 60°N and 83°N and at elevations of 40 to 1840 m above sea level. They encompass various environmental and climatic conditions, with permafrost temperatures that range from just below 0 to –15 °C. The substrates range from bedrock to fine-grained sediment with high ice content, and vegetation types include coniferous forests in the Mackenzie Valley, shrub tundra at high elevation in the southern Yukon Territory, and polar desert in the High Arctic. Permafrost conditions at all of these sites are determined primarily by air temperature, followed by snow and substrate conditions. The apparent thermal diffusivity is relatively high at colder sites and in bedrock and is lower at sites in sediment with high ice content. Snow has a greater influence on air–ground temperature relations at sites where mean annual air temperatures and active-layer moisture contents are relatively high, leading to physically significant latent heat effects and a slower freeze-back of the active layer.